PRAMIPEXOLE DIHYDROCHLORIDE LOADED MPEGPCL NANOSUSPENSION BY MODIFIED NANOPRECIPITATION: IN VITRO AND IN VIVO EVALUATION - SOMASUNDARAM I; SATHESH KUMAR S (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Abstract Aim and Objectives The present study was carried out to show the potential neuroprotective effects in both invitro and invivo pramipexole dihydrochloride nanosuspension for the treatment in Parkinson’s disease. Materials and Methods: Nanosuspension of pramipexole dihydrochloride was prepared with MPEG-PCL and Pluronic F68 by the process of modified nanoprecipitation technique with different concentrations of MPEG-PCL. The particle size, zeta potential, SEM, TEM and invitro dug release where performed. The cell viability study was performed by using SH-SY5Y cells. Further the formulation is evaluated for its antioxidant potential against rotenone induced neuronal damage in Wister rats such as enzymatic, non enzymatic antioxidants and histopathological evaluation. Result and Discussion: The nanoformulation shows least particle size of 143 nm and maximum zeta potential value 33.4 mv with 88.53% entrapment efficiency were observed with PMPNP 2 formulation. The SEM, TEM and invitro dug release of PMPNP 2 were shows spherical shape with controlled release when compared to other formulations. Further the MTT assay were performed by using SH-SY5Y cells which shows more than 50 % cell viability with 50 Âµl of PPMNP 2 nanoformulation. Further the antioxidant potential done in rotenone induced neuronal damage in Wister rats. The results showed elevation in the levels of enzymatic and non enzymatic antioxidants compared with neuronal toxic group. Further nanoformulation group showed decrease in levels of LPO which correlates with histopathological architecture. Conclusion: Our study concluded that nanoformulation showed better protective potential in both invitro and invivo compare to free drug for the treatment in Parkinson’s disease. Keywords: Pramipexoledihydrochloride; MPEG-PCL; SH-SY5Y cells; Nanoprecipitation; Parkinson’s disease.